2014
DOI: 10.1016/j.scitotenv.2013.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cocaine and nicotine metabolites in wastewater by liquid chromatography–tandem mass spectrometry. Cross abuse index patterns on a major community

Abstract: HIGHLIGHTSCross abuse index patterns on licit and illicit drugs by means of sewage assessment Data about cocaine and nicotine consumption from a Portuguese population Co-evaluation of cocaine abuse estimates based on local drug purity levels ABSTRACT A method based on sample preparation by solid phase extraction and analysis by liquid chromatography and mass spectrometry was validated and used for simultaneous analysis of cocaine, benzoylecgonine and cotinine in samples collected at the major wastewater treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 38 publications
4
24
0
1
Order By: Relevance
“…Generally, it can be stated that the average cotinine concentrations in wastewater in cities with over 80,000 inhabitants (Prague-2810 ng/L, Bratislava-2270 ng/L, Košice-1170 ng/L, České Budejovice-2720 ng/L a Nitra-3490 ng/L) (Table 3) correspond with the results obtained in other professional studies (Ort et al 2014;Mackuľak et al 2014;Thomas et al 2012), which measured average cotinine concentrations in cities like Zurich, Adelaide, and Lisbon in a range of 2590-3500 ng/L. In the study of Lopes et al (2014), a monitoring of cotinine was conducted for a period of 1 month and similarly to our data, it was found that the concentration of the compound in the wastewater varies considerably (1130-3500 ng/L). They also point out that the increase in concentration may occur during weekends and public or religious holidays due to significant migration of urban residents.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Generally, it can be stated that the average cotinine concentrations in wastewater in cities with over 80,000 inhabitants (Prague-2810 ng/L, Bratislava-2270 ng/L, Košice-1170 ng/L, České Budejovice-2720 ng/L a Nitra-3490 ng/L) (Table 3) correspond with the results obtained in other professional studies (Ort et al 2014;Mackuľak et al 2014;Thomas et al 2012), which measured average cotinine concentrations in cities like Zurich, Adelaide, and Lisbon in a range of 2590-3500 ng/L. In the study of Lopes et al (2014), a monitoring of cotinine was conducted for a period of 1 month and similarly to our data, it was found that the concentration of the compound in the wastewater varies considerably (1130-3500 ng/L). They also point out that the increase in concentration may occur during weekends and public or religious holidays due to significant migration of urban residents.…”
Section: Resultssupporting
confidence: 84%
“…Cotinine (CT) is afterwards further metabolized into several submetabolites, meaning that only 10-15 % of consumed nicotine is excreted as cotinine (Lopes et al 2014). Currently, several studies have addressed the occurrence of cotinine in the environment.…”
Section: Statistical Analysis Of Nicotine and Cotinine From Wastewatermentioning
confidence: 99%
See 2 more Smart Citations
“…This approach, called wastewater-based epidemiology (WBE), has been mainly applied in the last decade for estimating illicit drug consumption (Baker et al, 2014; Ort et al, 2014; Thomas et al, 2012; Zuccato et al, 2008) and more recently has also been proposed for the quantitative measurement of lifestyle habits such as tobacco and alcohol use, exposure to environmental and food contaminants or factors related to health and illness in a community (Lopes et al, 2014;Reid et al, 2011;Rodríguez-Álvarez et al, 2015;Rousis et al, 2017;Thomas and Reid, 2011; Yang et al, 2015). The main advantage of WBE is that it provides objective, up-to-date information about the use of these substances in a population and can therefore complement current epidemiological methods.…”
mentioning
confidence: 99%